2012
DOI: 10.3813/aaa.918559
|View full text |Cite
|
Sign up to set email alerts
|

On Measurements of Stage Acoustic Parameters: Time Interval Limits and various Source–Receiver Distances

Abstract: The most widely recognized objective stage acoustic parameters are the Early Support (ST early ) and Late Support (ST late ). In these parameters the early and late reflected sound energy is measured within a certain time interval. Different time interval limits have been proposed for the stage acoustic parameters but there is no agreement on the preferable limits. There is a growing interest to measure stage acoustic parameters at various source to receiver distances. In this paper the influence of perceptual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 14 publications
0
24
0
Order By: Relevance
“…This modification leads to differences (averaged over 10 concert hall stages) between ST early,d and ST early ranging from only 0.3 dB at position S4 close to the stage edge up to 2.7 dB for position S1 often close to 2 m from the back wall. 2 Results for the original ST early are also discussed in the current study. The difference between ST late,d and ST late is negligible: only 0.02 dB from an average of 11 concert hall stages.…”
Section: Stage Acoustic Parametersmentioning
confidence: 91%
See 4 more Smart Citations
“…This modification leads to differences (averaged over 10 concert hall stages) between ST early,d and ST early ranging from only 0.3 dB at position S4 close to the stage edge up to 2.7 dB for position S1 often close to 2 m from the back wall. 2 Results for the original ST early are also discussed in the current study. The difference between ST late,d and ST late is negligible: only 0.02 dB from an average of 11 concert hall stages.…”
Section: Stage Acoustic Parametersmentioning
confidence: 91%
“…For comparing early reflected sound levels on different stages, the exact choice of time limit is not that relevant. In an earlier paper, 2 it was shown that different time windows on either early or late reflected sound would not lead to a difference in ranking of eight different halls. Therefore, the extended and modified versions of the well-established ST parameters were a logical step and are considered being most appropriate for current research.…”
Section: Stage Acoustic Parametersmentioning
confidence: 97%
See 3 more Smart Citations